Liberal naturalism, objectivity and the autonomy of the mental. Issue 5 (28th May 2019) - Zapero, David
ABSTRACT: The paper distinguishes between two different ways of cashing out the general insight that often goes by the name of 'liberal naturalism'. The objective is to show how these two different argumentative strategies undergird two fundamentally different approaches to the project of elucidating the specificity of mental phenomena. On one approach, the central concern of such a project is the ontological status of subjective conscious phenomena; on the other, the central concern is the irreducibility of parochial capacities in the adoption of intentional stances. I begin by tracing out some of the origins of this important divergence and then focus on the motivations of the latter approach. I show that there is a tension between its motivations and the way that it has been used to rehabilitate idealist themes from the post-Kantian tradition.